BUGISMAKASSAR SEAMANSHIP AND REPRODUCTION OF MARITIME CULTURAL VALUES IN INDONESIA - Munsi Lampe (Humaniora, 2012)
Thisarticle is an initiative to develop the maritime anthropology field of study that up till now is stagnant and tends to be concerned with the surface structure of the maritime cultural phenomena. By application of the concept of reproduction maritime ethos disposition in explaining the navigational experience and maritime interaction of Bugis-Makassar seamen, some of their maritime cultural valuescan be discovered. Attitudes and main values such as knowledge and navigation skills, adaptation with physical environment and socio-culture, water spatial concept, brave and like adventure, hard working and competitive, honest and trustable, loyal and responsible, openness and freedom, strict to attitude and religious, collectivism, etc. which were applied in the trading and sailing activities of the Bugis-Makassar sailors can be understood as maritime cultural values. Indonesia maritime cultural values of Bugis-Makassar are also in the forms of awareness and diversity of values and relationships between ethnic groups and cultures, love to the country, language unity, and nationality. This article isbased on historical annotation of Bugis-Makassar seamenship and field work data from Bira (Bugis region) and Paotere (Makassar region) conducted in six months (from April to September 2010).Keywords: Bugis-Makassar seamen, seamenship experience, maritime culture reproduction.